The inclusion of disability and aging in COVID-19 hygiene behavior change interventions across low-and middle-income countries: A review using the COVID-19 Inclusive WASH Checklist - Wilbur, Jane; Ferdous, Sharika; Wapling, Lorraine (Frontiers in Public Health, 2022)
Introduction People with disabilities and older adults face a high risk of dying from COVID-19. Handwashing with soap and sanitising surfaces were recommended to disrupt COVID-19 transmission. Yet, in many low-and middle-income countries (LMICs), these populations have inadequate access to water, sanitation and hygiene (WASH) and are not reached by public health campaigns. The Hygiene Behaviour Change Coalition (HBCC) was set up to limit the spread of COVID-19 in LMICs. Twenty organisations working across 37 countries were funded to encourage populations to adopt recommended personal hygiene behaviours. This study aims to review the inclusion of disability, ageing, and caregiving in HBCC grantee interventions. Methods A COVID-19 Inclusive WASH Checklist, which incorporates core concepts of human rights, was developed to support the inclusion of disability, ageing and caregivers in interventions. The Checklist was applied to 137 documents submitted to donors within the HBCC fund to assess inclusion. Eligible grantee programme documents related to HBCC-funded projects were identified between August 2020 and January 2021. Feedback was provided to grantees recommending how to strengthen the inclusion of disability, ageing, and caregiving. Results Most organisations identified people with disabilities, older adults and caregivers as target groups, but targeted activities to include them were scarce. Where efforts were made, immediate needs rather than rights were addressed. For example, the construction of accessible handwashing facilities featured more prominently than ensuring the participation of these groups. Examples of the coverage of core concepts in interventions included generating data with these groups and developing interventions accordingly. Limitations to inclusion were inconsistent organisational approaches, inability to monitor media campaigns, and inadequate coverage of disability and ageing in donor’s grant funding mechanisms. Conclusion To ensure these populations benefit from efforts, they must be explicitly identified as target groups, with assigned actions that are monitored; efforts must go beyond accessible WASH services to ensure the meaningful participation of these groups. The COVID-19 Inclusive WASH Checklist supports this but requires further testing to assess its appropriateness and effectiveness.